Problems and damages in road and bridge structures, as well as increasing their bearing capacity with gabion structures (Международный научный журнал «Инженер», 2026)
This article examines the increase in the load-bearing capacity of road and bridge structures and the causes of failures. The scientific basis for the application of composite-type gabion structures in the protection of transport structures, protection from erosion, water flows, and other external factors is highlighted, and the purpose of this article is to review innovations in the field of bridge construction, to describe advanced materials and structural solutions. Possibility of sustainability, environmental safety with the help of gabions. Highly effective and universal methods of strengthening, stabilizing, and protecting slopes and road surfaces in operation using gabion structures, bridge cones, bridge supports, regulating dams, embankments, and other structures. The work on increasing the load-bearing capacity of gabion structures is considered.